Estimation of genetic variability and implications of direct and indirect effects of different traits on leaf yield in bathua (Chenopodium album) - PARKASH, CHANDER (The Indian Journal of Agricultural Sciences, 2012)
The present investigations were undertaken to study variability and analyze the inter-relationship among five quantitative characters in 60 indigenous and exotic germplasm lines of bathua (Chenopodium album). All the traits revealed a considerable amount of variation among the germplasm lines. The extent of variation ranged from 12.4–435.3 g/plant for leaf yield. The phenotypic coefficients of variation were higher than genotypic coefficients of variation for all the characters. The estimates of genotypic coefficient of variation were higher for number of leaves/plant (46.75%), followed by leaf width (47.07%) and leaf yield/plant (46.43%). Heritability estimates (H2) were high (>80%) for all the five characters. In spite of high heritability values for all the traits, the expected genetic advance as per cent of mean ranged from 35.86 to 95.01. The genotypic correlation coefficients were in general higher in magnitude than the corresponding phenotypic correlation coefficients. All the characters were positively correlated with leaf yield but significant and positive correlation with leaf yield were shown only by plant height and number of leaves/plant. Path coefficient analysis revealed that number of leaves had highest direct effect (0.6279) on leaf yield, followed by leaf length (0.1728) and direct selection could be made for these characters for improving leaf yield. Plant height showed maximum positive indirect effect (0.2084) via number of leaves towards leaf yield hence simultaneous selection for number of leaves/plant and plant height can be made for the improvement of leaf yield in bathua.